Parallel solution of the elastic-plastic problem using a tridiagonal algorithm for LU-decomposition from the ScaLAPACK library - Konovalov, Anatoliy Vladimirovich; Tolmachev, Arseniy Vladimirovich; Partin, Alexandr Sergeevich (Computational Continuum Mechanics, 2011)
The paper considers the parallel solution of the elastic-plastic problem using a tridiagonal LU-based solver from the ScaLAPACK library, including the solution of linear systems of equations. A brief description of the tridiagonal matrix algorithm is presented. The results of numerical experiments are given.
Keywords: elastic-plastic problem; parallel computing; ScaLAPACK